THE ROLE OF STRIATIONS IN PYRITE CRYSTAL GROWTH - Morgan B. (My University, 2002)
Presents an abstract of the article 'The Role of Striations in Pyrite Crystal Growth,' by B. Morgan presented at the 28th Rochester Mineralogical Symposium.
Keywords: PYRITES